Peran Lingkungan Bahasa Dalam Meningkatkan Maharah Kalam Mahasiswa: Kajian Literatur - Randy Randy (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This literature review examines the role of language environment (bi'ah lughawiyyah) in improving the maharah kalam (Arabic speaking skills) of university students. A language environment refers to any intentionally or naturally created setting in which students are exposed to and encouraged to use the target language in their daily interactions. Drawing on a systematic literature review of 23 research articles and relevant documents published between 2015 and 2024, this study identifies and analyzes the key dimensions, mechanisms, and evidence related to language environment and its effects on speaking competence. The findings demonstrate that a well-designed Arabic language environment—encompassing physical, programmatic, and social dimensions—significantly enhances students' speaking fluency, accuracy, and confidence. Specific programs such as Arabic dormitories (ma'had), language weeks, mufradat walls, and peer conversation partnerships have been empirically shown to increase the quantity and quality of students' Arabic speech production. The study also highlights that the social dimension of the language environment, particularly peer interaction and a supportive institutional culture, plays a more decisive role than the physical dimension alone. Challenges including inconsistent enforcement, low student motivation in non-residential settings, and limited teacher involvement outside the classroom are also discussed. This review recommends that Arabic language education programs at Indonesian universities develop integrated, multi-dimensional language environment policies to support maharah kalam development.